The Future of E-Health: Opportunities and Challenges in Public Health Systems - Toktas, Elif (Journal of Foresight and Health Governance, 2024)
This study aims to examine the opportunities and challenges of e-health implementation in public health systems, focusing on emerging digital health technologies, their impact on healthcare accessibility and efficiency, and the barriers that hinder their widespread adoption. This narrative review employs a descriptive analysis method, synthesizing literature from 2020 to 2025 on e-health advancements, policy frameworks, and implementation challenges. Data sources include peer-reviewed journal articles, government reports, and institutional white papers. The study categorizes findings into key themes, including telemedicine, mobile health (mHealth), electronic health records (EHRs), artificial intelligence (AI) in healthcare, blockchain for health data security, and virtual reality (VR) for medical training. The analysis also examines barriers such as privacy concerns, digital inequality, interoperability challenges, regulatory constraints, and resistance to change. E-health technologies have significantly improved healthcare accessibility, particularly in remote and underserved areas, by expanding telemedicine services and enabling mobile health applications. AI-driven diagnostics and big data analytics have enhanced early disease detection and public health decision-making, while blockchain technology has shown potential for strengthening data security and interoperability. However, concerns over cybersecurity threats, regulatory inconsistencies, and disparities in digital literacy continue to hinder the full integration of e-health. Additionally, healthcare providers' reluctance to transition to digital platforms and the high costs of implementation pose challenges to scalability. While e-health presents transformative opportunities for improving public health systems, its successful implementation requires addressing key challenges related to data security, policy standardization, and equitable access. Future efforts should focus on developing regulatory frameworks, enhancing digital health infrastructure, and fostering collaboration among stakeholders to ensure sustainable and inclusive digital health solutions.